THE EFECT OF BIOMECHANICAL KNOWLEDGE, PHYSICAL CONDITION, AND LANDING TECHNIQUE ON ACL INJURY RISK OF SEPAK TAKRAW ATHLETES - Abdul Aziz Hakim; Mulyana Mulyana; Sofyan Hanif (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
The purposes of this research are to obtain the effect of biomechanical knowledge, physical condition, and landing technique on ACL injury risk of sepak takraw athletes. This study was conducted at sepak takraw athletes of Jawa Timur Province. The numbers of 30 smasher athletes participated was chosen by total sampling technique. The data was collected has been analyzed by path analysis method test the hypothesis. The research finding are; (1) there is a direct effect of biomechanical knowledge on ACL injury risk, (2) there is a direct effect of physical condition on ACL injury risk, (3) there is a direct effect of landing technique on ACL injury risk, (4) there is a direct effect of biomechanical knowledge on landing technique, (5) there is a direct effect of physical condition on landing technique, (6) there is a non direct effect of biomechanical knowledge on ACL injury risk, (7) there is a non direct effect physical condition on ACL injury risk. Keywords: biomechanical knowledge, physical condition, landing technique, and ACL injury risk